1992
DOI: 10.1161/01.cir.85.3.1077
|View full text |Cite
|
Sign up to set email alerts
|

High-dose aspirin inhibits shear-induced platelet reaction involving thrombin generation.

Abstract: It is concluded that aspirin does affect the platelet response to shear forces, but this requires higher dosage (greater than 300 mg/day), suggesting a mechanism probably different from that of interference with thromboxane formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(69 citation statements)
references
References 32 publications
3
66
0
Order By: Relevance
“…Oral-Administration of Samples To evaluate the antithrombotic effect on rat blood, the MeOH extract, EtOAc sol- [28][29][30] On the basis of their published data, a three-channel haemostatometer was constructed by Yamamoto, et al, at the Faculty of Nutrition of Kobe Gakuin University for research purposes.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Oral-Administration of Samples To evaluate the antithrombotic effect on rat blood, the MeOH extract, EtOAc sol- [28][29][30] On the basis of their published data, a three-channel haemostatometer was constructed by Yamamoto, et al, at the Faculty of Nutrition of Kobe Gakuin University for research purposes.…”
Section: Plant Materialsmentioning
confidence: 99%
“…21,22 In various experimental settings aspirin has been shown to reduce thrombin generation. 12,23,24 Using the model of microvascular injury, it has been demonstrated that aspirin at a dose from 30 to 500 mg down-regulates thrombin formation in healthy subjects 15,25 and patients with CAD. 19,26 The purpose of the present study is to describe major coagulant events during blood clotting at the site of microvascular injury and to evaluate the effect of low-dose aspirin on the activation of prothrombin, FV, FXIII, and Fbg, and inactivation of FVa by APC.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in keeping with most, 15,23,25,26 though not all previous studies. 24 In contact pathway-inhibited whole-blood coagulation studied in vitro, high-dose aspirin administered in vivo had no effect on exclusively TF-induced coagulation. 45 This suggests that the aspirin effect in the present model may be tissueor shear-dependent.…”
mentioning
confidence: 96%
“…This test induces platelet-rich thrombus formation in non-anticoagulated (native) blood solely by shear forces, as opposed to conventional tests that use chemical agonists. Further, this test detects the spontaneous lysis of formed autologous thrombi in the same blood sample (15)(16)(17)(18)(19)(20).…”
Section: Effects Of Exercise On the Thrombotic State Assessed Using Nmentioning
confidence: 99%
“…Anticoagulants interfere with the mechanism of hemostasis and render the obtained results unphysiological. To overcome this limitation, some tests (shear-induced plateletrich thrombosis and thrombolysis tests) use nonanticoagulated whole blood (15)(16)(17)(18)(19)(20). The aim of the present review was to compare the effects of short-term and long-term exercise on the thrombotic state.…”
Section: Introductionmentioning
confidence: 99%